PENERAPAN METODE TILAWATI TERHADAP KEFASIHAN BACA AL-QUR’AN SISWA KELAS VII MTS NU TARBIYAH MUBALLIGHIN AL-ISLAMIYAH - Miftakhul Rohmah; Imam Safi’i; Ika Anggraheni (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Al-Qur’an learning is currently being pursued through formal (school), informal (family), and non-formal (community) education. On the formal path, namely at school, the Qur’an has become a sub-subject in the Islamic Religious. Education curriculum. The development of reading and writing the Qur’an is very broad and varied, but today’s young generation has limitations in science especially reading and writing the Al-Qur’an. The purpose of this study was to determine the ability to read the Qur’an of students at MTs Tarbiyah Muballighin al-Islamiyah Pujon is carried out before learning in the classroom by getting used to the dhuha prayer first. The tilawati method on fluency in reading the Koran properly and correctly, students also know the laws of tajwid the basics of religion. And students can also memorize verses of the Qur’an, memorize selected players for everyday life. And knowing makhorijul lettes, and reading Ghorib.